2020
DOI: 10.1038/s41598-020-75265-5
|View full text |Cite
|
Sign up to set email alerts
|

Climate-induced variability in South Atlantic wave direction over the past three millennia

Abstract: Through alteration of wave-generating atmospheric systems, global climate changes play a fundamental role in regional wave climate. However, long-term wave-climate cycles and their associated forcing mechanisms remain poorly constrained, in part due to a relative dearth of highly resolved archives. Here we use the morphology of former shorelines preserved in beach-foredune ridges (BFR) within a protected embayment to reconstruct changes in predominant wave directions in the Subtropical South Atlantic during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…In coupling the long-term millennial-scale Holocene evolution with modern wave data to infer a paleorecord based on shoreline orientation, this study contributes to studies about progradational systems in Australia and worldwide (e.g. Silva et al, 2020). The integration of paleo wave climate with additional insights on long-term changes in fluvial/tidal processes based on geomorphology was further used to determine control factors on barrier development.…”
Section: Context For the Studymentioning
confidence: 99%
“…In coupling the long-term millennial-scale Holocene evolution with modern wave data to infer a paleorecord based on shoreline orientation, this study contributes to studies about progradational systems in Australia and worldwide (e.g. Silva et al, 2020). The integration of paleo wave climate with additional insights on long-term changes in fluvial/tidal processes based on geomorphology was further used to determine control factors on barrier development.…”
Section: Context For the Studymentioning
confidence: 99%
“…According to Silva et al 2020, wave direction oscillations coexist with long-term variations in interhemispheric surface temperature anomalies, which indicates the influence of temperaturedriven atmospheric teleconnections on wave generation cycles. For instance, Reguero et al (2019) found inter-regional correlation of 0.54 between sea surface temperature (SST) variations in North and tropical Atlantic and WEF variations in extratropical South Atlantic.…”
Section: Introductionmentioning
confidence: 99%
“…The global climate has preferred patterns of variability, called climate modes. Climate modes, such as the Southern Annular Mode (SAM), El Niño-Southern Oscillation (ENSO) and the Atlantic Multidecadal Oscillation (AMO), are widely considered to be associated with typical natural climate variability at interannual to multidecadal scales, which is mainly reflected in variations in the patterns and distributions of the sea level pressure (SLP), wind and SST (Thompson and Wallace 1998;Kerr 2000;Trenberth et al 2002;Hurrell et al 2003;Hemer et al 2010;Silva et al 2020). The wave climate variability in different parts of the globe is modulated by one or a combination of several climate modes; thus, reliable projections of wave characteristics require an in-depth understanding of the relationships between climate modes and the wave climate.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to the hypothesis that increased wave energy may accelerate the release of sediments stored in coastal barriers to the subtidal shoals of tidal inlets, for instance when those are expending due to sea level rise. This would become even more relevant for establishing morphodynamic prediction of barrier systems along shores where the longshore sediment transport presents a climatically-driven variability (Almar et al, 2015;Anderson et al, 2018;Marchesiello et al, 2020;Poirier et al, 2017;Silva et al, 2020;Splinter et al, 2012;Wiggins et al, 2020). Another fundamental aspect for such morphodynamic predictions was found to be the reliance of the results on the bottom friction parameterization.…”
Section: From Barriers To Shoalsmentioning
confidence: 99%